IMPLEMENTASI KURIKULUM MERDEKA PADA PROSES PEMBELAJARAN DI SDN X BATUSANGKAR - Miftahul Jannah (JURNAL MINDA, 2023)
The background of this research is the implementation of the merdeka curriculum in the learning process. This research was conducted with the aim of describing how the form of implementation of the merdeka curriculum in the learning process of grade 4 students at SDN X Batusangkar city. In this study the method used is a qualitative research method. The type of research used in this research is a case study. The informants in this study were fourth grade elementary school teachers using a purposive sampling technique. The key instrument of this research was the researchers themselves, and the researchers also used tools such as cameras and interview instruments. Data collection techniques used are observation techniques, interviews and documentation. The data analysis technique uses the Miles and Huberman model which consists of three stages, namely the data reduction stage, the data display stage and drawing conclusions. The data validity assurance technique uses a technical triangulation technique. The results obtained from the research conducted can be concluded that the form of independent curriculum implementation in the learning process is by giving freedom to students and in learning students make images according to their respective interests and also by doing ice breaking, reflection and making agreements with students in learning.